Computer simulation in physics and engineering - Steinhauser, M. O. (Walter de Gruyter GmbH & Co. KG, 2013)
This work is a needed reference for widely used techniques and methods of computer simulation in physics and other disciplines, such as materials science. The work conveys both: the theoretical foundations of computer simulation as well as applications and ""tricks of the trade"", that often are scattered across various papers. Thus it will meet a need and fill a gap for every scientist who needs computer simulations for his/her task at hand. In addition to being a reference, case studies and exercises for use as course reading are included.